The Influence of Proactive Personality and Emotional Intelligence on Career Adaptability Through Self-Efficacy as a Mediator - Febrianti, Nelvita; Widodo, Slamet; Hadi, Effed Darta (Program MM Universitas Surabaya, 2026)
Purpose: his study examines how proactive personality and emotional intelligence influence career adaptability, with self-efficacy as a mediating variable among employees of Bank Bengkulu. The research offers novelty by integrating both personal traits and emotional competencies within a single framework to explain adaptive career behavior in a highly dynamic banking environment. Method: A quantitative explanatory design was employed using a survey of 440 employees from 10 Bank Bengkulu branches. Data were analyzed through Partial Least Squares Structural Equation Modeling (SEM-PLS) to test direct and mediating relationships among proactive personality, emotional intelligence, self-efficacy, and career adaptability. Result: The findings reveal that proactive personality and emotional intelligence positively affect career adaptability, both directly and indirectly through self-efficacy. Self-efficacy serves as a significant psychological bridge linking personal traits to adaptive career outcomes. Future research should explore this model across different organizational contexts and include additional mediating factors such as resilience or organizational support.